A)         f(x)= 6x+7x^(11) find f^(-1)(-13)= ? find (f^(-1))'(-13)= ?   B) g(x)=x^(2)-8x+22 for x is an element of [4, positive infinity) find g^-1(7)= ? find (g^-1)'(7)=?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

(1) We are given that `f(x)=6x+7x^11` .

(a) We are asked to find `f^(-1)(-13)` . One way would be to compute the inverse function and evaluate at x=-13. This is very difficult. It is much easier to realize that for an inverse function; `f(f^(-1)(x))=f^(-1)(f(x))=x` .


Here, we can find an x such that f(x)=-13. We get `6x+7x^11=-13` . By inspection we have x=-1, so the point (-1,-13) lies on the graph of f(x). Thus the point (-13,-1) lies on the graph of `f^(-1)(x)` .

The value of `f^(-1)(-13)=-1`

(b) In order to find `(f^(-1))'(-13)` we use the fact that `(f^(-1))'(x)=1/(f'(f^(-1)(x)))` . With `f'(x)=6+77x^10` we get:


So the value of `(f^(-1))'(-13)=1/83`

(2) We are given `g(x)=x^2-8x+22` , for x>4.

(a) Again it is difficult to find `g^(-1)(x)` . We find ` ` :




`=>x=5` or `x=3` . x=3 is not in the domain, so we have the point (5,7) on g(x). Thus the point (7,5) lies on the graph of `g^(-1)(x)` .

Thus the required value is `g^(-1)(7)=5`

(b) Using the theorem cited above, and `g'(x)=2x-8` we get:


Then the required value is `(g^(-1))'(7)=1/2`

Approved by eNotes Editorial Team

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial